2016
DOI: 10.1124/jpet.116.233106
|View full text |Cite
|
Sign up to set email alerts
|

Vascular and Central Activation of Peroxisome Proliferator-Activated Receptor-  Attenuates Angiotensin II-Induced Hypertension: Role of RGS-5

Abstract: Activation of peroxisome proliferator-activated receptor-b/d (PPARb) lowers blood pressure in genetic and mineralocorticoid-induced hypertension. Regulator of G-protein-coupled receptor signaling 5 (RGS5) protein, which interferes in angiotensin II (AngII) signaling, is a target gene to PPARb. The aim of the present study was to examine whether PPARb activation in resistance arteries and brain tissues prevents the elevated blood pressure in AngII-induced hypertension and evaluate the role of RGS5 in this effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…These findings are consistent with earlier observations that PPARγ agonist treatment improves pregnancy outcome in preeclamptic rats [44], and provide the first genetic evidence for a direct control of blood pressure homeostasis by PPAR-mediated transcriptional regulation of RGS5. Furthermore, PPARβ agonist treatment also ameliorates AngII-induced experimental hypertension in mice via upregulation of RGS5 [78].…”
Section: The Angii-ppar-rgs5 Signaling Axismentioning
confidence: 98%
“…These findings are consistent with earlier observations that PPARγ agonist treatment improves pregnancy outcome in preeclamptic rats [44], and provide the first genetic evidence for a direct control of blood pressure homeostasis by PPAR-mediated transcriptional regulation of RGS5. Furthermore, PPARβ agonist treatment also ameliorates AngII-induced experimental hypertension in mice via upregulation of RGS5 [78].…”
Section: The Angii-ppar-rgs5 Signaling Axismentioning
confidence: 98%
“…PPAR␤ activation attenuates the pressor and sympathoexcitatory actions of ANG II in the brain by inhibiting NADPH oxidase activity through a mechanism involving regulator of G protein signaling 5 (RGS5) (876). ANG II infusion decreases PPAR␥ DNA-binding activity in the brain, while activation of PPAR␥ in the brain blunts pressor response to systemically administered ANG II (1223).…”
Section: Sympathoexcitatory Actionmentioning
confidence: 99%
“…A recent study demonstrated that activated PPARδ attenuates Ang II-triggered hypertension by targeting regulator of G-protein-coupled receptor signaling 5 [19]. Based on this observation and our previous findings concerning the protective effects of PPARδ in the vasculature, we hypothesized that ligand-activated PPARδ may affect Ang II-induced vascular hypertrophy, a critical phenotype in hypertension.…”
Section: Introductionmentioning
confidence: 70%